Disclosure of Diagnosis and Prognosis to Cancer Patients in Traditional Societies: A Qualitative Assessment from Lebanon - James Feghali; Hussein El Semesmani; Abdallah Abboud; Lily Chacra; Khalil Choucair; Madelin Fenianos; Lama Al Jebbawi; Farah El Sayed; Faysal Kak; Salim M. Adib (Journal of Epidemiology and Public Health, 2019)
Background: